Energy cooperation between Russia and Latin America in the 21 century: Evidence from the activity of «Power Machines PJSC» in Argentina and Brazil - Mikhail Samsonov (Ибероамериканские тетради, 2018)
The paper analyzes the activity of the Russian company «Power Machines PJSC» in Argentina and Brazil as an example of the Russian – Latin American energy cooperation in the 21st century. In this work, the chronology of the Russian company’s activity in the aforementioned Latin American countries has been established, with the relevant statistical data being provided as well. The strengths and weaknesses of the Russian company in review are also determined in the course of this work, with the current state of the Latin American energy market being taken into consideration. In the concluding part of the article, several case scenarios regarding the future of «Power Machines PJSC» in Argentina and Brazil are presented.In the course of this paper, the following methods of research have been used: the historical method, the comparative method and the tabular method. The SWOT analysis method was also used.The research has found that while «Power Machines PJSC» has proven to be a reliable supplier of equipment for the power plants in Argentina and Brazil (and will likely continue to function as such in the medium term), its future largely depends on whether Argentina and Brazil make the shift towards the renewable energy or the nuclear energy.